Pattern of maxillofacial fractures in a Tertiary Referral Centre in Central Kerala - A comparison between the Pre-COVID and COVID periods - George Philip; Shiney Dominic; Anish Poorna T; Joshna EK (Elsevier, 2022)
Our aim was to observe if there was any appreciable difference in the etiology and pattern of maxillofacial fractures during the pre-COVID-19 and COVID-19 periods in Central Kerala, South India. This retrospective study was conducted with data over a period of two years from the central database registry of our hospital. Age, sex, etiology, date of injury, and site of facial fractures were recorded and compared between both the time periods. Increase in facial fractures due to fall at home (p value < 0.01) and decrease in mass casualty cases (p value < 0.01) were observed during the COVID-19 period. Pedestrians involved were significantly more in the pre-COVID-19 period (p value < 0.01) and heavy vehicle accidents producing facial fractures were significantly more in the COVID-19 period (p value < 0.01). Frontal bone (p value = 0.008), nasal bone (p value < 0.001) and zygomatico-maxillary complex fractures (p value < 0.001) occurred significantly more in the COVID-19 time period whereas naso-orbito-ethmoidal (p value = 0.003), mandibular (p value = 0.011) and dentoalveolar fractures (p value < 0.001) were seen significantly more in the pre-COVID-19 period. There was decrease in the total number of maxillofacial cases during the COVID-19 period. However, this was not significant when only the number of facial fractures were compared between the two periods. This study provided an insight on the differences in etiology and pattern of maxillofacial fractures during the pre-COVID-19 and COVID-19 periods. Road traffic accidents involving two wheelers predominate during the COVID-19 period also, prompting further critical exploration of the reasons behind this finding.